Hydrogeological simulation of head changes of a south Benin artesian aquifer - KPEGLI, Raoul; de Louw, Perry G.B.; ALASSANE, ABDOU KARIM; MAMA, DAOUDA (My University, 2022)
Artesian basins include groundwater that may rise above the land surface with free-flow conditions which make it possible to exploit groundwater without pumping. The change to non-artesian conditions may have large implications for local people using artesian wells for drinking and other purposes. We applied a 3D physically based model to assess future head developments in the Turonian-Coniacian artesian (T.C.) aquifer of southern Benin under different artesian outflows and climate scenarios. A sensitivity analysis of the hydraulic and storage properties of the subsurface layers was performed to determine the importance of each property. Results revealed that artesian basins are structured into peripheral and central zones behaving differently to external stresses. Head amplitudes in the peripheral zones which are adjacent to recharge zones are higher and decrease towards the central artesian zones due to the influence of the confined aquifer’s hydraulic diffusivity and the leakance of the confining layer. Based on the regional climate model (RACMO) that better reproduces the historical rainfall in the study area, lower recharge is predicted for the period until 2030 and will lead to head drops by 1 m at the peripheral artesian zone. However, such head drops will likely recover during the period 2030–2050 for which higher recharge is predicted. If the current artesian outflows double by 2050 this would cause heads to reduce by only a few centimeters both in the central and at the periphery of the artesian zone. Among all the subsurface layers properties, the hydraulic conductivity of the confined T.C. aquifer is most influencing the simulated heads across the artesian zone and its specific storage is revealed as the least influencing one.
Keywords: Artesian; Artesian outflows Benin; Groundwater recharge; Modeling